Epidemiology of Childhood Witnessing Domestic Violence and Exploration of Its Relationships With Affective Lability and Suicide Attempts in Chinese Young Adults - Gong, Jingbo (Journal of interpersonal violence, 2022)
Childhood witnessing domestic violence (CWDV) exerts short- and long-term negative impacts on emotional and behavioral health. The present study investigated the epidemiological features of CWDV, and its negative impact on psychological outcomes in a sample of Chinese college students. The mediating role of emotion regulation strategies on CWDV associations with psychological outcomes and gender differences in these relationships were examined. A total of 3,126 respondents (1,034 males; 2,086 females; 6 missing data in gender) completed the study questionnaire, which included demographic characteristics, CWDV, and suicide attempt history items as well as the Emotion Regulation Questionnaire (ERQ) and Affect Lability Scale-18 (ALS-18). Overall, 43.03% of the respondents reported CWDV, including 44.87% of males and 42.09% of females. Higher frequencies of CWDV were found to be related to the following factors: unstable marital status of parents; not being an only child; being a left-behind child, family financial difficulties, consumption of alcohol in the past year, and being in relatively poor physical condition. Among males, ERQ suppression scores were significantly higher for those men who experienced ?often or every day? CWDV than for men who indicated that they did not have any history of CWDV (Bonferroni-corrected p = 0.047). More frequent CWDV was associated with higher ALS-18 scores and increased risk of suicide attempts in males and females (p < 0.05), and emotion regulation (suppression) was found to mediate the association between CWDV and affective lability among males. This study revealed high rates of CWDV, and serious impacts of CWDV on mental health in male and female Chinese college students. In males, but not females, emotion regulation strategy use, use of suppression, was found to act as a mediator in the association of CWDV with affective lability. Our findings suggest that interventions for individuals with CWDV should focus on the emotional regulation, which may help them improve mental health, especially in males.